Climate Change and Groundwater: Impact, Adaptation and Sustainable - Lal, Manohar; Sau, Bhajan Lal; Patidar, Jitendra; Patidar, Abhishek (International Journal of Bio-resource and Stress Management, 2018)
Water is indispensable for life, but its availability at a sustainable quality and quantity is threatened by many factors, in which climate plays a leading role. Groundwater is the major source of water across the world for life particularly in rural areas of arid and semi-arid regions, but there has been very little research conducted on the potential effects of climate change.Continuous groundwater depletion of the states Gujarat, Punjab, Haryana, Tamil Nadu and Rajasthan that have registered groundwater development above the national average. The most prevalent form of irrigation in India is groundwater irrigation. Already 70% of Indian crop production is dependent on groundwater irrigation. The last 100 years, the global climate has warmed by an average of 0.5 °C due to higher concentrations of greenhouse gases in the atmosphere. Indian landmass below the Ganges plain is likely to experience a 0.5–1 °C rise in average temperatures during 2020–2029 and it will be rise up to 3.5–4.5 °C at the end of century. Kharif (monsoon) season crops will experience more risk of flood as well as droughts. Rabi and especially summer crops will experience enhanced ET, needing larger, more frequent irrigation because of climate change. Adaptation to climate change and improving sustainability include improved management and governance of large irrigation systems by focusing on demand management rather than supply management. Climate change have severe adverse impact on India’s precipitation patterns, ecosystems, agricultural potential, forests, water resources, coastal and marine resources. Large-scale planning would be clearly required as adaptation measures for climate change impacts, if catastrophic human misery is to be avoided and need to be mitigate the impact of climate change by adopting all possible management practices and save the ground water to sustain the future life. If the above practices were not implicated it show drastic effect on climate change which lead to cause adverse condition to living and non-living beings in developing country such as India.